2019
DOI: 10.1177/2374373519850971
|View full text |Cite
|
Sign up to set email alerts
|

Water on Fire: The Patients’ Lived Experience of Primary Percutaneous Coronary Intervention

Abstract: Background: The success of a coronary angioplasty in the treatment of myocardial infarction is affected by patients' experiences. However, the experiences of the people with an emergency angioplasty have remained unknown. Objective: This study was conducted to explore the patients' experiences of an emergency angioplasty. Method: This study was performed using the qualitative research method and interpretive phenomenological approach. Nine patients under emergency angioplasty were selected using purposeful sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…[19] Diğer kardiyak kateterizasyon sonrası hastaların deneyimlerinin incelendiği çalışmalarda da hastalar işlem konusunda bilgi sahibi olmadıklarını ve bu durumun anksiyeteye sebep olduğunu bildirmiştir. [20,21] Eğitimin hemşireler tarafından verilmemesinin nedenleri arasında hemşirelerin eğitici rolünü benimsememeleri ya da yoğun iş yükleri olabileceği düşünülmektedir.…”
Section: Bilgi Eksikliğiunclassified
“…[19] Diğer kardiyak kateterizasyon sonrası hastaların deneyimlerinin incelendiği çalışmalarda da hastalar işlem konusunda bilgi sahibi olmadıklarını ve bu durumun anksiyeteye sebep olduğunu bildirmiştir. [20,21] Eğitimin hemşireler tarafından verilmemesinin nedenleri arasında hemşirelerin eğitici rolünü benimsememeleri ya da yoğun iş yükleri olabileceği düşünülmektedir.…”
Section: Bilgi Eksikliğiunclassified
“…Yet, to date, this topic has attracted little attention from researchers. To the best of our knowledge, only three studies 17‐19 have explored the lived experiences of patients who have undergone PCI with stent implantation, and these studies have considered elective procedures only. The first study involved 15 patients, and the results showed that the patients were satisfied with the PCI procedure because it was a valid alternative to open‐heart surgery and that it was associated with both shorter recovery time and shorter hospital stay 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the patients experienced a “sense of need” due to their lack of education as well as due to the emotional and economic issues they faced 17 . In yet another study, Javadi‐Pashaki et al 18 analysed the lived experiences of patients who needed an emergency PCI intervention. They have identified five themes that describe the patients' experiences under the main theme “water on fire”: “diagnosis shock,” “being in an emergency situation,” “trying to self‐control,” “the need for reassuring care,” and “stability.”…”
Section: Introductionmentioning
confidence: 99%